Treatment decisions in metastatic colorectal cancer: beyond first and second line combination therapies - Vogel, Arndt; Hofheinz, Ralf-Dieter (Cancer treatment reviews, 2017)
Median overall survival (OS) of patients with metastatic colorectal cancer (mCRC) has reached up to 30months in recent clinical trials of first line therapies. Following disease progression after the standard in both, 1st and 2nd line, combination chemotherapy with monoclonal antibodies, many patients maintain a good performance status and a significant proportion is motivated to undergo further therapy. Choices of treatment beyond the second line setting for mCRC are therefore becoming increasingly important. New options have entered the therapeutic field recently: Regorafenib is a multikinase inhibitor approved for mCRC patients who have progressed on chemotherapy (including fluoropyrimidines, irinotecan, and oxaliplatin), plus VEGF inhibitor(s) and - if RAS wild-type - an anti-EGFR inhibitor. Regorafenib significantly improved OS, compared to placebo, in two phase III trials (CORRECT and CONCUR) in mCRC patients. Trifluridine/Tipiracil, an oral fluoropyrimidine, also resulted in significantly improved OS when compared to placebo in the phase III RECOURSE trial, which was conducted in a similar patient population to CORRECT. Reintroduction of previously administered therapy is another valid and commonly used approach, especially for those regimens which were discontinued before progression, e.g. if associated with cumulative toxicities, such as peripheral neuropathy or due to treatment breaks. Re-challenge of drugs to which patients developed resistance is also feasible although evidence for this strategy is limited.
Gesehen am 08.10.2018
Available online 4 May 2017